Osteopoikilosis: a rare case with interesting imaging - Mohammad, Nejadhosseinian; Pouya, Hadighi; Leila, Aghaghazvini; Ali, Mozaffari Mohammad; Mazyar, Babagoli; Tahereh, Faezi Seyedeh (Archives of Case Reports, 2023)
Background: Osteopoikilosis (OPK) is a rare osteosclerotic dysplasia. It is usually asymptomatic and diagnosis is made incidentally by radiographic findings. It has a unique radiographic presentation with multiple small, well-defined, circular, or ovoid radiodensities which are distributed symmetrically in the epiphysis and metaphysis of long bones. Aim of the work: In this case report, a 38-year-old man with mild joint discomfort was diagnosed with OPK according to his radiographic findings and literature review. Conclusion: It is important to diagnose OPK and to distinguish it from other medical conditions to calm the patient and to reduce unnecessary investigation.